LAS NORMAS INTERNACIONALES DE CONTABILIDAD, ANÁLISIS Y TRATAMIENTO DE LA NIC No. 2 INVENTARIOS EN TEXTILES MAR Y SOL S.A. PERIODO MAYO-JUNIO 2016 - Agurto Sarmiento, Daniel Alejandro (2018)
The purpose of this thesis is to comply with the last requirement of the National University of Loja for the professional title of C.P.A. Therefore, an analysis of the treatment of inventories is carried out in the company Textiles Mar y Sol, the objective being to know if a correct adaptation of IAS 2 is being carried out in the company, since, at present, the adequate application of the International Accounting Standards is essential for the preparation of financial statements that reflect the real situation of the organization, providing reliable data for decision making. In order to comply with the established objectives, a summary of all the international accounting standards was carried out, in order to know the basic principles about their treatment. Subsequently, through a comparative table, the differences between the warehouse and accounting records were determined, in terms of the entry and exit of inventories, with the purpose of identifying the existing errors, as well as establishing their effects on the company. In addition, a matrix showed the impact of negative balances within the organization and how these values affect it economically. Finally, using a cost sheet, which included the three items manufactured by Textiles Mar y Sol, control mechanisms and recommendations were defined to solve the problems detected. Based on the analysis of the results obtained, control methods were established for the inventories account of the Textiles Mar y Sol S.A., in order to reduce the economic impact of the inadequate record of their inventories.